Effect of Change in Management, Organizational Culture and Transformational Leadership on Employee Performance PT. AdhyaTirta Batam (PT. ATB) - Sinaga, Hendrik Gomar; Asmawi, Moch.; Madhakomala, R.; Suratman, Adji (International Review of Management and Marketing, 2018)
A company that can survive and thrive (going concern) is a company that can empower various Human Resources potential optimally in achieving their best performance thus increasing the ability to be better than other organizations. The purpose of this study was to examine the Effect of Change Management, Organizational Culture and Transformational Leadership on Employee Performance PT. Adhya Tirta Batam (PT. ATB), using path analysis method in a quantitative approach. The sample of this research was 233 employees of PT. ATB. The results of this research indicate that there is a direct effect of Management Change on Employee Performance which is worth 17.7%, there is a direct effect of Organizational Culture on Employee Performance which is worth 17.8%, there is a direct effect of Transformational Leadership on Employee Performance which is worth 20.6%, there is an indirect effect of Change Management on Employee Performance through Transformational Leadership that is worth 3.8%, there is indirect effect of Organizational Culture on Employee Performance through Transformational Leadership which is 5.1%. Thus it can be explained that the most direct influence on Employee Performance is Transformational Leadership. Keywords: Change Management, Organizational Culture, Transformational Leadership, Employee Performance JEL Classifications: M12, M54, N75 DOI: https://doi.org/10.32479/irmm.7081